A Helical Metamaterial for Broadband Circular Polarization Conversion. Issue 10 (23rd June 2015) - Kaschke, Johannes; Blume, Leonard; Wu, Lin; Thiel, Michael; Bade, Klaus; Yang, Zhenyu; Wegener, Martin
<x xml:space="preserve">Abstract</x> Metallic helical metamaterials give rise to broadband and scalable chiro‐optical effects orders of magnitude higher than found in nature. While arrays of gold helices have been suggested as compact circular polarizers, where a large difference of the diagonal elements of the Jones transmission matrix is desired, chiral metamaterials can also be designed to exhibit strong circular‐polarization conversions. Here, a novel helical metamaterial design, exhibiting asymmetric, broadband circular‐polarization conversion, is introduced. The metamaterial is composed of unit cells with a single helix that changes its handedness halfway along the helix axis. Based on numerical calculations, an intuitive model explaining the principle of operation is given. Furthermore, a novel fabrication approach employing STED‐inspired direct laser writing in combination with electrochemical deposition of gold is presented. The experimental data show circular‐polarization conversion of up to 75% for an unmatched bandwidth of one octave, in very good agreement with theory.